1978
DOI: 10.1103/physrevlett.41.152
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Backward Peak inp-He4Elastic Scattering at 1.05 GeV

Abstract: p-^Ue elastic scattering has been measured at 1.05-GeV incident proton energy, close to 180° in the center of mass. The steep backward peak observed at lower energies is still present, but its slope appears to decrease.Our previous results on elastic p-4 H.e scattering at intermediate energies and at angles close to 180° in center-of-mass system revealed the occurrence of a sharp rise in the differential cross section, which became steeper as the energy increased. 1 Various theoretical models have tried to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Here the 4 in the denominator comes from the factor two higher charge of 4 He nuclei compared to 3 H nuclei. Altogether it is found that energetic 4 He contributes only of the order ∼ 6% to the final 6 Li abundance This is also not changed by the existence of a sharp backward scattering peak in N -4 He scattering [74] which, similarly to the possible existence of a backward peak in the 3-nuclei distribution (see above) may increase the 6 Li synthesis due to energetic 4 He by a factor ∼ 1.2.…”
Section: Non-thermal Fusion Reactionsmentioning
confidence: 68%
See 2 more Smart Citations
“…Here the 4 in the denominator comes from the factor two higher charge of 4 He nuclei compared to 3 H nuclei. Altogether it is found that energetic 4 He contributes only of the order ∼ 6% to the final 6 Li abundance This is also not changed by the existence of a sharp backward scattering peak in N -4 He scattering [74] which, similarly to the possible existence of a backward peak in the 3-nuclei distribution (see above) may increase the 6 Li synthesis due to energetic 4 He by a factor ∼ 1.2.…”
Section: Non-thermal Fusion Reactionsmentioning
confidence: 68%
“…[64] a fraction of about 2% of all spallation reactions seem to result in 3 H nuclei at the kinematically highest allowed energy. This corresponds to backward scattering and such peaks in the distribution functions are also observed in 4 He-4 He elastic scatterings [74]. If the four-event backward scattering peak as observed in Ref.…”
Section: Non-thermal Fusion Reactionsmentioning
confidence: 96%
See 1 more Smart Citation